Translation, cultural adaptation, and validation of the Nurse Self-Concept Questionnaire (NSCQ) for Portuguese nursing students - Inês F. Almeida; Rafael A. Bernardes; Liliana B. Sousa; Paulo Santos-Costa; Filipa Ventura; Amorim Rosa (BMC, 2024)
Abstract Background The professional self-concept of nursing students significantly influences their attitude and identity within the profession, ultimately impacting their mental health and overall well-being. Recent evidence underscores the importance of assessing students' professional self-concept to prevent adverse outcomes such as burnout and stress. Since there are currently no validated instruments available in Portugal for this purpose, our objective was to translate, adapt, and validate the Nurse Self-Concept Questionnaire (NSCQ) with nursing students in Portugal. Methods A two-phase research study with a non-probabilistic sample of 216 undergraduate nursing students, using the Qualtrics XM electronic platform for data collection. An exploratory factor analysis was performed to verify the validity of the theoretical construct and its internal consistency. Cronbach's alpha was calculated, and a confirmatory factor analysis was performed to assess the model fit. Results The final instrument, designated as Questionário de Autoconceito dos/as Enfermeiros/as (Pt - NSCQ), is composed of 24 items distributed across five dimensions: "General self-concept", "Staff relations", "Leadership", "Communication-care" and "Knowledge", which explain 67.71% of the total variance. All dimensions and the global scale revealed good internal consistency values, ranging from 0.775 to 0.927. The resulting factorial structure is coherent with the theoretical framework. Conclusion The Pt - NSCQ proved to be a valid and reliable instrument to assess Portuguese nursing students' professional self-concept. Future studies should be carried out on larger samples and different educational contexts, aligned with the importance to ensure the continuity of the psychometric analysis of the instrument.